Implementation of Human Resource Management in Improving the Quality of Education in MAN 1 Kab. Sukabumi: Implementasi Manajemen Sumber Daya Manusia Dalam Peningkatan Mutu Pendidikan di MAN 1 Kab. Sukabumi - Nurhasanah, Dede; Nugraha, Mulyawan Safwandy (Tinta Emas Publisher, 2023)
This study seeks to identify the implementation of human resource management in improving the quality of education, as well as the factors that support the implementation. This research was conducted at MAN 1 Kab. Sukabumi using qualitative descriptive methodology. The findings of this study show that the implementation of Human Resource Management to Improve the Quality of Education consists of several stages, including a) needs and information analysis, b) teacher recruitment, c) induction of new employees, d) teacher placement, e) granting authority and responsibility for staff, f) implementing supervision, g) providing teacher welfare, h) employee career development, termination of employment, and j) rewarding. While the Supporting Factors are a) the principal has many considerations, b) programs implemented in schools can bring changes and positive impacts, c) facilities and infrastructure can be utilized optimally, and d) there is an evaluation, the Proposal Factors are a) the principal has many considerations, b) programs implemented in schools can bring changes and positive impacts.